RECOVERY, GROWTH AND CARCASS COMPOSITION FOLLOWING PERIODS OF RESTRICTED RATION AND FULL FEEDING IN INDIAN MAJOR CARP, ROHU (LABEO ROHJTA H.) - Prabhakar, Surya Kumar; Sardar, Parimal; Shah, Mukhtar Hussain (Journal of Indian Fisheries Association, 2006)
A 90-day experiment was conducted to determine the effect of restricted ration and full feeding on the recovery growth and carcass compositions ofÂ fingerlings (average weight- 20.74 Â± 0.13 g) of rohu, Labeo rohita (H.). RohuÂ fingerlings procured from a local fish breeder were fed with commercialÂ pelleted feed (27o/o crude protein) during the two-week acclimatization in theÂ laboratory condition. Experimental pelleted diet (30% crude protein) wasÂ prepared and the control group (TcFR) was fed at 3o/o of body weight for the 90-Â day trial period. The experimental group T, ..R was fed for three days at 1 <% ofÂ body weight and the next three days at 3o/c) of body weight, T2m was fed forÂ seven days at 1 o/o of body weight and the next seven days at 3% of body weight, T3m was fed for 15 days al l ’/ of body weight and the 15 days at 3o/o of bodyÂ weight and T4FR was fed for 25 days at 1 o/o of body weight and the next 25 days atÂ 3o/o of body weight, alternating between 1 and 3(% for the specified periodÂ during the 90-day trial period. Daily rations were divided into two equalÂ meals per day at 09.00 and 16.00 hours. Average percent survival rate of rohuÂ during the 90-day tr-ial period was more than 90. Percent live weight gainÂ (98.90 Â± 0.34, 113.0 Â± 5.93, 125.71 Â± 11.01 and 141.90 Â± 2.89), specific growthÂ rate (1.53 Â± 0.0 L J.(,R :L 0.06, 1.80 Â± 0.10 and 1.96 Â± 0.02Â°/o/d) and absoluteÂ growth rate (1.33 Â± 0.1.1, l.JX ! 0.07. 1.3’) Â± 0.04 and 1.44 Â± 0.07 g/d) of theÂ experimental groups (T,FR’ T2m, T3m and T_.m, respectively) increased with theÂ advancement of the experiment in comparison to those in control, Tcm (90.92 Â±Â 5.81 o/o, 1.44 Â± 0.07o/o/d and 1.34 Â± 0.20 g/d, respectively) and wereÂ proportionately correlated with the degree of deprivation probably throughÂ the mechanism of increasedJeed intake (hyperphagia), feed efficiency ratio orÂ gross growth efficiency, protein efficiency ratio and the superior feedÂ conversion ratio reflecting in better performance index. The body length andÂ muscle composition of fish indicated that recovery growth happened due toÂ protein growth but certainly not due to fat deposition in the gut. Feeding at 1Â and 3% of body weight alternating over a period of25 days might economizeÂ the culture operation ofrohu. Keywords: Recovery growth, feed deprivation, fuU feeding, carcass composition, rohu (Labeo rohita)